Electron-hole Fermi liquid in nanosized semiconductor structures - Litovchenko, V.G.; Grygoriev, A.A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2010)
The experimental and theoretical results on the quantum-sized electron-hole
liquid plasma (EHLP) in semiconductors and analysis of the difference of it in
comparison to the bulk one have been presented. The non-equilibrium Fermi EHLP can
be created in the bulk and layered structures (insulator-semiconductor interfaces, thin
films, quantum superlattices, etc.) at low temperatures and powerful laser radiation. In
the quantum-sized structures, however, these phenomena appear at much higher
temperatures, up to the room ones. The peculiarities of EHLP phenomena are:
(1) appearance the very broad luminescence line in the low-energy side of its spectrum,
which have constant width and energy position under variation of the light intensity as
well as narrowing peak when increasing the temperature; (2) appearance of stimulated
radiation with a relatively low excitation threshold (the so-called “surface laser effect”);
(3) planar ballistic expansion of electron-hole plasma over long distances; (4) predicted
effect of transformation of non-equilibrium 2D plasmons into radiative modes.